Umsonst ›gegeben‹? (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
This book is based on the thesis that everything we understand by experience, including and especially the experience that questions us the most, as in shame, can only be clarified as far as possible in the social context of a socially sensitized culture of dissent. This culture must take an eminent interest in how others see the "Sa-chen" of phenomenology, more or less differently than we do ourselves. In this perspective, twenty preliminary studies to the "Fundamental Questions of Hermeneutic Anthropology", published in 2024 and based on Ricœur's life's work, are presented as supplements to these basic questions. They address the phenomenology and hermeneutics of the 20th century from M. Merleau-Ponty, J.-P. Sartre and P. Ricœur to J.-L Marion, H. Blu-menberg and B. Waldenfels consistently from a socio-philosophical perspective.